No toy, no joy? – Some reflections on the potential of toy-free week to promote children’s creativity and active learning - Grażyna Kiliańska-Przybyło; Beata Górkiewicz (Journal of Early Childhood Education Research, 2017)
The article presents the results of the project entitled ‘Toy-free week’ in which children, (aged 5-6) were engaged in constructing their own toys from various materials, including waste materials. These toys were later used in group-work activities or individual free play. Play is an indispensable element for children’s learning and growing up. However, encouraging children to design their own toys from available materials allows them to identify their creative abilities and it fosters creativity development. The aim of the project was to examine how children would react to the idea of toy-free week and cope with a lack of ready-made toys. Besides, involving children in preparation of their own toys was supposed to raise their awareness about other possibilities of playing. In addition, toy preparation and construction was believed to facilitate their independence and responsibility for what they were doing. The article aims at describing the procedure of the project, discussing its benefits and drawbacks as well as answering to what an extent toy free education is welcomed by children.